Drugs and biologics receiving FDA orphan drug designation: an analysis of the most frequently designated products and their repositioning strategies. (2nd December 2021) - Miller, Kathleen L.; Kraft, Selma; Ipe, Abraham; Fermaglich, Lewis
ABSTRACT: Background: The Orphan Drug Act was created to stimulate the development of drugs and biologics for rare diseases. Investigating products that have received orphan drug designation provide a greater understanding of rare disease drug development, as well as the repositioning business models of developers. Research design and methods: We used a dataset containing all orphan drug designations between 1983 and 2019. To analyze the orphan products, we constructed a variable, 'unique product, ' that allowed for the standardization of generic names of drugs and biologics. Additional analysis was performed on the most frequently designated unique products and their repositioning strategies. Results: We found 5, 099 orphan drug designations representing 3, 269 unique products, of which 508 had an orphan-designated approval from FDA. Unique products with only a single designation represented 2, 448 (75%) of the total products and 26 (1%) products had 10 or more designations. Over 60% of these unique products with 10 or more designations were antineoplastics or immunomodulators. Conclusions: The most designated unique products revealed a continuum of repositioning strategies, from the repurposing of approved drugs to parallel indication development programs for recently developed drugs. The fact that over 3, 000 unique products have been studied for rare diseases indicates that future repositioning opportunities may become increasingly available.